Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Guru Swasta di Medan - Akman Daulay; Eka Umi Kalsum (Economics, Business and Management Science Journal, 2021)
This research explaints about organizational culture and leadership style on teacher performance at Yayasan Nasional Perguruan Brigjend Katamso Medan. The theory used in this research includes the theory of organizational culture, leadership style and performance. The population in this study were teacher at Yayasan Perguruan Nasional Brigjend Katamso Medan as many as 53 people. The data analysis model used is multiple regresion analysis. This research method uses descriptive quantitative supported by a survey and is explanatory. The results of the research by testing t-test hypothesis show the organizational culture has a positive and significant effect on teacher performance at Yayasan Perguruan Brigjend Katamso Medan. Leadership style has a positive and significant effect on teacher performance at Yayasan Perguruan Brigjend Katamso Medan. F test results show that the organizational culture and leadership style have positive and significant effect on teacher performance at Yayasan Perguruan Brigjend Katamso Medan. The value of the coefficient of determination of organizational culture and leadership style is able to explain the teacher performance variable of 82.6 % and the remaining 17.4 % is influenced by other variables not examined in this study.